Creating a framework for material selection of polymers to use in trucks - Hjartardóttir, Ingibjörg Anna; Makam, Roshni Vijaykumar (My University, 2023)
An in-depth analysis of the creation of a material selection framework, specifically highlighting the transition from fossil-based polymers to renewable alternatives. Volvo Group Trucks requires a sustainability-driven material selection tool that takes material properties into consideration, enabling informed choices within a shorter time frame. The data utilized for constructing the framework was obtained from structured interviews. This material selection represents a systematic analysis that impacts product performance, expenses, and environmental repercussions. It underlines the importance of choosing polymeric materials, emphasizing the criteria used in the selection process and its contribution to achieving sustainability goals. By considering aspects like mechanical properties, cost- effectiveness, accessibility, and environmental implications, this approach can narrow down the most fitting polymeric materials for Volvo truck components. This approach symbolizes a structured material selection method, advancing sustainable practices and responsible resource utilization within the Volvo Group. The report’s structure begins with the theoretical and research methodology. Subsequently, a section dedicated to the interview findings that played an important role in shaping the material selection framework. Later in the report, there is a comprehensive explanation of the framework’s structure, and its effectiveness is assessed through a dedicated case study. Finally, the discussion section involves an analysis of the case study results and an explanation of the findings.
Keywords: material selection framework; Sustainable polymer selection